PETROGENESIS OF SILICIC MAGMATISM RELATED TO THE ~2.44 GA RIFTING OF ARCHEAN CRUST IN KOILLISMAA, EASTERN FINLAND - Lauri L.S.; Rämö O.T.; Huhma H.; Mänttäri I.; Räsänen J. (My University, 2006)
Early Paleoproterozoic extension in the Archean craton of the Fennoscandian shield led to the emplacement of several 2.44 Ga layered gabbroic intrusive complexes in northern Finland and adjacent Russia. Closely associated with them are felsic rocks of similar age: (1) the Sirniö Group volcanic rocks on top of the Koillismaa layered complex; (2) a quartz alkali feldspar syenite at Kynsijärvi near the Koillismaa complex; and (3) an aluminous A-type granite at Nuorunen near the Oulanka layered complex. In the Koillismaa area, the ruptured Archean crust consists of ortho- and paragneisses that were intruded and migmatized by somewhat younger granites. U-Pb zircon data indicate that the gneisses are at least ~2.8 Ga old and that the granites were crystallized at ~2.7 Ga. Both rock types show a common monazite age of 2695 Ma that registers the peak of granulite facies metamorphism and, possibly, the intrusion of the granites. The local Neoarchean crust has εNd(at 2440 Ma) values between -5 and -8.5. The mafic rocks of the Koillismaa complex show initial εNd(at 2440 Ma) values around -1.5 and those of the Oulanka complex range from 2.1 to 0. The εNd value (-4.8) and TDM model age (2.9-3.0 Ga) of the Kynsijärvi quartz alkali feldspar syenite are within the limits of the evolution path of the local Archean crust. The corresponding values for the Nuorunen granite are -2.0 and 2.76 Ga and are thus closer to those of the mafic rocks. The volcanic rocks of the Sirniö Group show more scatter with initial εNd(at 2440 Ma) values of -1.1 to -5.3; the lowest εNd values probably reflect later disturbance-magmatic values cluster around -2. Major and trace element modeling shows that fractional crystallization of the Koillismaa complex parental magma or partial melting of the Archean crust cannot account for the ~2.44 Ga silicic rocks of Koillismaa. The geochemical and Nd isotope characteristics of the volcanic rocks and the Kynsijärvi quartz alkali feldspar syenite are best explained by a combined assimilation-fractional crystallization model involving a contaminated komatiitic parental magma and intermediate-mafic lower crustal assimilant. Differences in the initial Nd isotope composition of the 2.44 Ga rocks reflect varying source components and evolutionary history for the Archean lithosphere in eastern Fennoscandia. © 2005 Elsevier B.V. All rights reserved.
Keywords: ARCHEAN; FINLAND; KOILLISMAA; ND ISOTOPES; OULANKA; PALEOPROTEROZOIC; RIFTING; U-PB AGE; Precambrian::Archean; Докембрий::Архей; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская